Prevalence of Self-Reported Lifetime History of Traumatic Brain Injury and Associated Disability: A Statewide Population-Based Survey. Issue 1 (January 2016) - Whiteneck, Gale G.; Cuthbert, Jeffrey P.; Corrigan, John D.; Bogner, Jennifer A.
Abstract : Objective: To investigate the prevalence of all severities of traumatic brain injury (TBI), regardless of treatment setting, and their associated negative outcomes. Participants: A total of 2701 adult Coloradoans. Design: A statewide, population-based, random digit–dialed telephone survey. Main Measures: The lifetime history of TBI was assessed by a modification of the Ohio State University TBI Identification Method; activity limitation and life satisfaction were also assessed. Results: The distribution of self-reported lifetime injury was as follows: 19.8%, no injury; 37.7%, injury but no TBI; 36.4%, mild TBI; and 6.0%, moderate-severe TBI. Of those reporting a TBI, 23.1% were hospitalized, 38.5% were treated in an emergency department, 9.8% were treated in a physician's office, and 27.5% did not seek medical care. A clear gradient of activity limitations and low life satisfaction was seen, with the highest proportions of these negative outcomes occurring in people reporting more severe TBI and the lowest proportions in those not reporting a TBI. Approximately twice as many people reported activity limitations and low life satisfaction after nonhospitalized TBI compared with hospitalized TBI. Conclusions: This investigation highlights the seriousness of TBI as a public health problem and the importance of including all severities of TBI, no matter where, or if treated, in estimating the prevalence of disability co-occurring with TBI.